Does perceived teacher affective support matter for middle school students in mathematics classrooms? - SAKIZ, GÖNÜL (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
The purpose of the present study was to explore the importance of perceived teacher affective support in relation to sense of belonging, academic enjoyment, academic hopelessness, academic self-efficacy, and academic effort in middle school mathematics classrooms. A self-report survey was administered to 317 seventh- and eighth-grade students in 5 public middle schools. Structural equation modeling indicated significant associations between perceived teacher affective support and middle school students motivational, emotional, and behavioral outcomes. The structural model explained a significant proportion of variance in students' sense of belonging (42%), academic enjoyment (43%), self-efficacy beliefs (43%), academic hopelessness (18%), and academic effort (32%) in mathematics classrooms. In addition to providing the basis for a concise new measure of perceived teacher affective support, these findings point to the importance of students' perceptions of the affective climate within learning environments for promoting academic enjoyment, academic self-efficacy, and academic effort in mathematics. (C) 2011 Society for the Study of School Psychology. Published by Elsevier Ltd. All rights reserved.
Keywords: Teacher affective support; Sense of belonging; Academic self-efficacy; Academic enjoyment; Academic hopelessness; Academic effort in mathematics; PERSON-ENVIRONMENT FIT; SELF-EFFICACY; ACADEMIC ENGAGEMENT; CHILD RELATIONSHIPS; MOTIVATION; ACHIEVEMENT; PREDICTORS; PERCEPTIONS; ADOLESCENTS; RELATEDNESS